Learners' Ecoliteracy Based on Structure of Observed Learning Outcomes (SOLO) Taxonomy: (Ekoliterasi Peserta Didik Berdasarkan Taksonomi Structure of Observed Learning Outcomes) - Suryanda, Ade; Heryanti, Erna; Syaikhan, Azika Aulia Hanizya; Lestari, Hilda Nur Indah (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
The research aims to determine the differences in ecoliteracy of high school students majoring in science and social studies. Ecoliteracy in students is needed to form a sustainable society, and requires a basic understanding of ecology and ecosystem principles. SOLO Taxonomy (Structure of Observed Learning Outcomes) is used to determine students' responses in their understanding of ecoliteracy. This research uses a qualitative descriptive method with a comparative causal approach. The research sample came from students majoring in science and social studies for the 2018/2019 academic year at 3 public high schools in Bekasi. The results show that there is a difference in the ecoliteracy of high school students majoring in science and social studies, the average ecoliteracy score of students majoring in science is 179, while the average ecoliteracy score of social studies students is 169. The SOLO taxonomy level of science students is at the relational and abstract levels. expanded and the SOLO taxonomy level of social studies students is at the multistructural level up to the expanded abstract. The conclusion of this research is that there are differences in the ecoliteracy of students majoring in science and social studies which are reviewed based on the SOLO Taxonomy. ABSTRAK Penelitian bertujuan untuk mengetahui perbedaan ekoliterasi peserta didik SMA jurusan IPA dan IPS. Ekoliterasi pada peserta didik diperlukan untuk membentuk masyarakat berkelanjutan, dan diperlukan pemahaman dasar tentang ekologi serta prinsip ekosistem. Taksonomi (Structure of Observed Learning Outcomes) SOLO digunakan untuk mengetahui respon peserta didik dalam pemahamannya mengenai ekoliterasi. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan kausal komparatif. Sampel penelitian berasal dari peserta didik jurusan IPA dan IPS Tahun Ajaran 2018/2019 di 3 SMA Negeri di Bekasi. Hasil menunjukkan bahwa terdapat perbedaan ekoliterasi peserta didik SMA jurusan IPA dan IPS rata-rata skor ekoliterasi peserta didikÂ jurusan IPA adalah 179 sedangkan rata-rata skor ekoliterasi peserta didik IPS adalah 169. Tingkatan level taksonomi SOLO peserta didik IPA berada pada level relasional dan abstrak yang diperluas dan tingkat level taksonomi SOLO peserta didik IPS berada pada level multistruktural sampai dengan abstrak yang diperluas. Kesimpulan dari penelitian ini adalah terdapat perbedaan ekoliterasi dari peserta didik jurusan IPA dan IPS yang ditinjau berdasarkan Taksonomi Structure of Observed Learning Outcomes (SOLO).